MODEL OF ORGANIZATION OF STUDENTS’ SCIENTIFIC AND RESEARCH ACTIVITY - V. Y. Stromov; P. V. Sysoyev (Высшее образование в России)
One of the tasks of higher educational institutions at the present stage is training of qualified specialists who on graduating from university can engage in research and innovation activities in the professional sphere to create innovative products, organize science intensive industries and introduce modern scientific achievements into practice. However, the effectiveness of solving this problem directly depends on the organization of students' research activities during their studies at university. This paper focuses on the issues concerning involvement of students into research work and the development of a corresponding multilevel model of the organization of students' research activities at the university. The authors a) indicate the importance ofthe issue, b) generalize the goals and objectives of the development of students' science at university, c) develop a multilevel model for organizing students' research activities at university, d) consider the effectiveness of students' research work managing at university.